Public Health News Appraisal: An Approach to Content Analysis of News Article on Public Health - Patel, Mehul; Bhardwaj, Pankaj; Saxena, Deepak; Joshi, Nitin; Kumar, Nitesh; Singh, Kuldeep; Gaidhane, Abhay; Zahiruddin, Quazi Syed; Jain, Yogesh (Annals of the National Academy of Medical Sciences (India), 2021)
Public Health News Appraisal (PHNA) is a systematic process and an important skill to be mastered by public health trainees by which the strengths, weaknesses, and validity of a news article can be identified. This process helps trainees to identify usefulness of news, recognize any potential for bias, and ascertain whether the news is trustworthy. Trainees can assess whether the news article successfully communicates the intended message to reader. PHNA checklist with 18 questions was designed to help students to achieve this objective. Responses of most of the questions in this checklist are in the form of yes, no, and can’t tell. The articles can be categorized and analyzed based on the comparative PHNA score.
Keywords: public health; content; newspaper article; evaluation